Sebaceoma of the lip originating in Fordyce's spot - A rarity - Anuradha Calicut Kini Rao; Bhavna Nayal; Sushmitha Malpe Gopal; Manna Valliathan; Rajgopal Shenoy (Our Dermatology Online, 2016)
Introduction: Sebaceomas are relatively rare benign neoplasms differentiating towards sebaceous glands. These dermal neoplasms present as solitary papule or nodule. The age of presentation is sixth to ninth decade with a female preponderance. They may be associated with underlying visceral malignancies. We present a case of sebaceoma of the lip. This case is being presented because of its rare site of occurrence. Case report: A seventy five year old lady presented with a single, well defined, painless and progressively enlarging flesh coloured papule over the upper lip of two months duration. No systemic signs or symptoms suggestive of visceral malignancy were present. Clinical diagnosis of papilloma was proferred. Histopathological examination of the excision biopsy revealed nests and lobules of basaloid cells and few mature sebocytes seeming arising from central hyperplastic sebaceous gland. Final diagnosis of sebaceoma was rendered. Conclusion: Sebaceoma is an adnexal tumour typically affecting the face and the scalp. To the best of our knowledge, this is the first case to be reported in literature in the lip. The possible origin of sebaceoma in the present case could be ectopic sebaceous glands (Fordyce's spots) which occur in increasing frequency in elderly individuals, especially in the lip